A Cross-Sectional Study of Iranian EFL Learners' Realization of Request Speech Acts - Mahani, Solmaz Taghizade (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: The present cross-sectional study contributes to the research to date on interlanguage pragmatics by exploring Iranian EFL learners‟ realization of requestive speech acts compared to that of British English native speakers. Specifically, the study examined the requestive behavior of Iranian EFL learners from four different English proficiency levels in terms of directness, as well as the social variables of power and distance to reveal their pragmatic development, if any, in the target language learning. To this end, a Discourse Completion Test (Jalilafar, 2009), as well as Cross-cultural Speech Act Realization Project (CCSARP) (Blum-Kulka et al., 1989) were employed to elicit and code requestive interlanguage data from 115 Iranian EFL learners, as well as English baseline data from 10 British native speakers, respectively. The study findings revealed that there was evidence of pragmatic development across the English proficiency levels of the Iranian learners in terms of directness as well as in relation to the situational variable of power. However, in terms of the strategy selection and frequency of strategy use, as well as the social variable of distance the EFL learners exhibited requestive performance somewhat different from that of the native speakers. In this regard, the advanced level learners, compared to the other levels, showed requestive production closer to that of the British participants. Yet, the Iranian learners at this and lower levels required further development of their pragmatic competence. In conclusion, this study provides some implications for more effective pedagogy in EFL contexts, as well as suggestions for prospective research. Keywords: interlanguage pragmatics, pragmatic competence, pragmatic development, request speech act, request strategies. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu kesitsel çalışma dillerarası edimbilimsel araştırmalarına katkıda bulunmak amacıyla yapılmıştır. Bu bağlamda araştırma, anadili Farsça olan ve İngilizce dil eğitimi gören öğrencilerin rica sözeylemi gerçekleştirmelerini anadili İngilizce olan katılımcılarla karşılaştırarak ortaya cıkarmaya çalışmıştır. Özellikle, direktlik seviyesinde ve güç/tanışıklık sosyal etkenleri açısından farklı İngilizce yeterlik düzeyinde İranlı öğrencilerin rica sözeylemlerinde edimbilimsel gelişmenin olup olmadığı incelenmiştir. Bu amaca uygun olarak 115 İranlı öğrenciden dillerarası verilerin ve 10 anadili İngilizce olan katılımcıdan İngilizce kaynak verilerin toplanması icin Söylem Tamamlama Aracı (Jalilafar, 2009) ve verilerin kodlanmasi için CCSARP Projesi (Blum-Kulka, House ve Kasper, 1989) kullanılmıştır. Çalışmanın sonuçları, İranlı öğrencilerde direktlik seviyesi ve durumsal farklılaşma gösteren güç etkenleri açısından İngilizce yeterlik düzeyi ile orantılı olarak kullanımbilimsel gelişimin olduğunu göstermiştir. Fakat, İranlı öğrenciler rica sözeylemini gerçekleştirirken, tanışıklık etkeni, strateji seçiminde ve uygulama sıklığında, anadili İngilizce olan katılımcılardan daha farklı rica davranışları sergilemiştir. Bu bağlamda, ileri seviyedeki öğrenciler, alt seviyedeki öğrencilere göre İngiliz katılımcılara daha yakın rica performansı göstermiştir. Buna karşın, her iki düzeydeki öğrencilerin kullanım yeterliği konusunda daha çok yol katetmeleri gerekmektedir. Sonuç olarak, bu araştırma, İngilizce‟nin yabancı dil olarak kullanıldığı kontekstler için verimli olabilecek eğitsel öneriler ve dillerarası edimbilim alanında yapılacak araştırmalara ışık tutacak öneriler sunmaktadır. Anahtar kelimeler: Dillerarası edimbilim, edimbilimsel yeterlik/gelişme, rica sözeylemi, rica stratejileri.
Master of Arts in English Language Teaching. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching (ELT), 2012. Supervisor: Assoc. Prof. Dr. Gülsen Musayeva Vefalı.
Keywords: English Language Teaching; English Foreign Language - Study and Teaching - Iranians; Interlanguage Pragmatics - Pragmatic Competence - Pragmatic Development; Request Speech Act - Request Strategies